E-Commerce Based Technopreneurship For Developing Sales Of Small And Medium Industrial Products - Suranto Suranto; Adcharina Pratiwi (Jurnal Info Sains : Informatika dan Sains, 2023)
Research at the Masaran Sragen batik industry center aims to formulate a set of technopreneurship marketing strategy models based on digital e-commerce in order to increase product sales capacity in small and medium industries. The benefits of the research resulted in the formulation of a model and implementation of batik marketing that is goodness of fit and effectively implemented. The research object was carried out at the SME batik industry center Masaran Sragen. Data collection methods are through questionnaires, observations, interviews and direct activities at batik IKM. The analysis method is by formulating a digital marketing implementation model, e-commerce, through regression to determine the influence of indicators for implementing digital marketing strategies on increasing the sales capacity of batik products. Digital marketing strategy variables include: company website (X1), TikTok social media account (X2), Instagram social media account (X3), Facebook social media account (X4), digital marketing marketplace (Shopee) X5, product catalog (X6), YouTube social media account (X7), company nameplate promotion (X8) and company profile (X9) and business capacity variable in the form of sales volume (Y). Based on the analysis, a formulation of a marketing technopreneurship implementation model based on digital goodness of fit was produced, digital marketing market place (shopee) dominantly influences increasing sales capacity, overall the implementation of digitalization variables influences increasing sales volume.